Thermal and wine processing enhanced Clematidis Radix et Rhizoma ameliorate collagen Ⅱ induced rheumatoid arthritis in rats. (24th April 2022) - Jiang, Si-Qi; Pan, Ting; Yu, Jia-Lin; Zhang, Ying; Wang, Ting; Li, Ping; Li, Fei
Abstract: Ethnopharmacological relevance: Clematidis Radix et Rhizoma, a kind of traditional Chinese medicine, is derived from Clematis chinensis Osbeck, Clematis hexapetala Pall. and Clematis manshurica Rupr. This herb shows great effects on expelling wind and dispelling dampness in ancient and it has anti-inflammatory and analgesic activity in modern clinical application. Aim of the study: This experiment aimed to research anti-rheumatoid arthritis effect of crude and wine processed RC based on glycolysis metabolism to provide new ideas treating RA. Materials and methods: Network pharmacology was applied to preliminarily forecast the potential pathways of common targets of RC and RA. RAW264.7 macrophages were induced by LPS, NO production, glucose uptake, lactate production, ROS and MMP were detected as instructions in vitro. ELISA was used to measure the content of HK2, PKM2 and LDHA involving in glycolysis process. Gut microbiota was analyzed by 16S rRNA gene amplicon sequencing in CIA rats. Results: Crude and wine processed RC had good anti-inflammatory effect by reducing NO in RAW264.7 macrophages and ameliorating inflammatory infiltration and cartilage surface erosion in CIA rats. Whether in LPS-induced macrophages or CIA rats, crude and wine processed RC could inhibit glycolysis by down-regulating the expression of PKM2, causing less glucose uptake and lactic acid, which lead to less ROS and higher MMP to normal. PI3K-AKT and HIF-1α pathways were deduced to possibly play a crucial part in controlling glycolysis metabolism by network pharmacology analysis. Besides, it was displayed that Firmicutes and Bacteroidetes were prominent gut microbiota in CIA rats feces. CC-H and PZ-H groups could both increase the relative abundance of Firmicutes and decrease Bacteroidetes . These microbiota also played a role in RA pathological process via involving in energy metabolism, carbohydrate metabolism and immune system. Conclusion: Crude and wine processed RC have a good influence in ameliorating rheumatoid arthritis by inhibiting glycolysis and modulating gut microbiota together. Graphical abstract: Image 1 Highlights: Thermal and wine processed RC had good anti-inflammatory effects to ameliorate RA in vitro and vivo. Thermal and wine processed RC inhibited glycolysis via mainly decreasing PKM2 in vitro and vivo. The gut microbiota Roseburia and Prevotella were related with glycolytic enzyme PKM2 and LDHA. PI3K-AKT pathway and HIF-1α pathway were deduced to be closed with glycolysis metabolism by network pharmacology analysis. Thermal and wine processed RC may treat RA through inhibiting glycolysis combined with modulating gut microbiota.